Pelaksanaan Asesmen HOTS Dalam Pembelajaran Sejarah Pada Jenjang Sekolah Menengah Atas Di Kecamatan Tanjung Senang Bandar Lampung - yosi nadia (Journal of Social Science Education, 2020)
This study is based on the implementation of the 2013 Curriculum which requires the application of HOTS questions. Therefore, this study observed how the HOTS assessment was implemented in history learning at high school level in the Tanjung Senang district, Bandar Lampung. The purpose of this study was to determine the implementation of HOTS assessment in history learning at high school level. in the Tanjung Senang District of Bandar Lampung. The method used in this research was qualitative with descriptive data analysis. The informants in this study were history teachers at Tanjung Senang Senior High School, Bandar Lampung. The results showed that the history teachers had implemented HOTS questions, but still having problems, so that the implementation of HOTS questions by the history teachers in SMA Tanjung Senang Bandar Lampung was still categorized sufficient because the evaluation questions given in its implementation were adjusted to the students' abilities.